Financing Italy’s Cultural Heritage Sites - Suhan, Allison (Ge-conservacion, 2017)
With fifty World Heritage sites, Italy is fiscally responsible for more World Heritage sites than any other country in the world. The country has seen many years of economic uncertainty, and the need for heritage site maintenance continues. In recent years, unique funding strategies such as fee structures, tax incentives, and public-private partnerships have been utilized to counteract the deteriorating culture budget and support Italy’s architectural assets. Through case studies of World Heritage Sites in Italy, the research for this paper examined ways the country has balanced this monetary responsibility through these strategies. These projects are on-going and ever-changing, thus making them particularly relevant for the most current cases to explore. The research results in a recommendation of how to finance lesser-known sites and how the financing tools utilized in Italy can be applied elsewhere.